SISTEM ADMINISTRASI PAJAK PENGHASILAN (PPH) PASAL 21 KARYAWAN PADA PT. PERKEBUNAN NUSANTARA XIV (Persero) PABRIK GULA TAKALAR - Kamaruddin DP (AkMen JURNAL ILMIAH, 2017)
This study aims to determine how the calculation, reporting and payment of Income Tax Article (VAT) 21 employees at PT. Plantation Nusaantara XIV (Persero) Sugar Factory Takalar.Untuk know the documents used in the system of administration of Income Tax (VAT) of article 21 on the PT. Perkebunan Nusantara XIV (Persero) Sugar Factory Takalar.Sedangkan analysis method used is descriptive method quantitative Check and examine the data collected to ascertain whether the data can be accounted for righteousness. Categorize the data adjusted to the new criteria and the things needed in a data collection. How to measure and calculate it using quantitative descriptive analysis. The results of this study adalahPada system administration Income tax (VAT) of Article 21 at PT. Perkebunan Nusantara XIV (Persero) Takalar sugar factory in accordance with the provisions set Pajak.Proses administration Directorate General of Income Tax (VAT) of Article 21 at PT. Perkebunan Nusantara XIV (Persero) Takalar Sugar Factory are as follows: Checking the supporting documents, Noting taxation, Making tax calculation, Make a list of evidence to withholding tax (VAT) of Article 21, Archiving evidence withholding tax (Income Tax) of Article 21. docu- documents used in the report and pay income tax (VAT) of Article 21 as follows: Notice Period (return period), the Annual Tax Return (SPT Annual), Tax Payment (SSP).